2010
DOI: 10.1002/etc.413
|View full text |Cite
|
Sign up to set email alerts
|

Mercury and methylmercury concentrations in two newly constructed reservoirs in the Wujiang River, Guizhou, China

Abstract: We studied the distribution of different mercury species in two newly created reservoirs (Hongjiadu [HJD] and Suofengying [SFY] Reservoir) within the Wujiang River, Guizhou Province, China. These reservoirs were sampled four times between January, 2007, and November, 2007. Water, soil, and fish tissue samples were collected and analyzed for organic (methylmercury) and total Hg. Dissolved organic carbon (DOC) content in water was measured as well. In both reservoirs, the DOC concentration was low (range 0.5-4.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 34 publications
(25 reference statements)
2
18
0
Order By: Relevance
“…With the relatively low anti-interference ability and little ecological stability, the new reservoir cannot have enough strong self-purification or water environmental bearing capacities to purify the input nutrients. Then, the large inputs of nutrients accelerated the growth of algae, especially cyanobacteria and the weak new reservoirs ecosystem cannot maintain the ecological balance (Smith et al 1999;Yao et al 2011;Smayda 2008).…”
Section: Comparison With the Mature Reservoirmentioning
confidence: 99%
See 1 more Smart Citation
“…With the relatively low anti-interference ability and little ecological stability, the new reservoir cannot have enough strong self-purification or water environmental bearing capacities to purify the input nutrients. Then, the large inputs of nutrients accelerated the growth of algae, especially cyanobacteria and the weak new reservoirs ecosystem cannot maintain the ecological balance (Smith et al 1999;Yao et al 2011;Smayda 2008).…”
Section: Comparison With the Mature Reservoirmentioning
confidence: 99%
“…These fragile and unstable ecosystems accelerate water environment deterioration. Some new reservoirs even show eutrophication during the first impoundment (Camargo et al 2005;Yao et al 2011). So does the nutrient loading play a role in eutrophication as important as it does in mature reservoirs?…”
Section: Introductionmentioning
confidence: 99%
“…The Baihua Reservoir, which has a recent history of Hg pollution caused by waste water discharges from the Guizhou organic chemical plant (GOCP), utilising metallic Hg as a catalyst to produce acetic acid, exhibited high levels of total-Hg in the water body and in underlying sediments (Feng et al, 2003c(Feng et al, , 2004dHou et al, 2004;Yan et al, 2005). In a comparison between an up to 30 years old reservoir (Wujiangdu Reservoir) and newly constructed ones (Hongjiadu and Suofengying Reservoirs), the latter category exhibits slightly lower MMHg concentrations (Yao et al, 2011). He et al (2008a) conducted a long-term monitoring study of the Hg load in inflows and the outflow of the Hongfeng Reservoir and found a good comparison concerning the MMHg concentration in the flows with the exception for the summer period when the MMHg level in the outflow was up to 6 times higher than that in inflows ( Fig.…”
Section: Lakes and Reservoirsmentioning
confidence: 99%
“…Louis et al, 2004). In Guizhou, the area flooded after establishment of a new reservoir generally consisted of farmlands with a meagre organic matter content (1.9% to 4.1% for the Hongjiadu and Suofengying reservoirs (Yao et al (2011)). Hence, the limited access to fresh organic material may curb the establishment of active environments for biomethylation.…”
Section: Lakes and Reservoirsmentioning
confidence: 99%
See 1 more Smart Citation